Architecting angular applications with redux, RxJS, and NgRx: learn to build redux style high-performing applications with angular 6 - Noring, Christoffer (PACKT Publishing, 2018)
Managing the state of large-scale web applications is a highly challenging task with the need to align different components, backends, and web workers harmoniously. When it comes to Angular, you can use NgRx, which combines the simplicity of Redux with the reactive programming power of RxJS to build your application architecture, making your code elegant and easy to reason about, debug, and test. In this book, we start by looking at the different ways of architecting Angular applications and some of the patterns that are involved in it. This will be followed by a discussion on one-way data flow, the Flux pattern, and the origin of Redux. The book introduces you to declarative programming or, more precisely, functional programming and talks about its advantages. We then move on to the reactive programming paradigm. Reactive programming is a concept heavily used in Angular and is at the core of NgRx. Later, we look at RxJS, as a library and master it. We thoroughly describe how Redux works and how to implement it from scratch. The two last chapters of the book cover everything NgRx has to offer in terms of core functionality and supporting libraries, including how to build a micro implementation of NgRx.